Mapping the ESG – CFP Nexus : Bibliometric, Thematic, and Meta-Analytical Synthesis - Saxena, Payal; Begde, Prasad (Indian Journal of Finance, 2026)
Purpose : The objective was to analyze ESG performance and firms’ corporate financial performance using bibliometric and meta-analytic methods to identify the most influential authors, journals, and articles in the field and to calculate the financial impact of environmental, social, and governance (ESG). Methodology : A total of 1,128 documents were sourced from the Scopus database and refined using PRISMA to conduct a bibliometric analysis. Of these, 550 articles were included in the meta-analysis using a random-effects model. Findings : We reported a growing trend in the publication examining the relation between ESG and Corporate Financial Performance (CFP) literature. The meta-analysis results indicated a positive relationship between ESG and CFP. Practical Implications : The findings suggested that managers, investors, and policymakers should recognize firms’ practice of ESG criteria as it creates long-term firm value and sustainable financial performance. Originality : This study was among the first to integrate bibliometric, thematic, and meta-analysis to examine ESG–CFP relationship, thereby advancing previous literature.